سلوك مؤسسة الاسمنت – تبسة بين خطورة الملوثات البيئية لصناعة الاسمنت وتكاليف مواجهتها – دراسة تقييمة للفترة ( 2010- 2015 ) . - سمايلي, نوفل; بوطورة, فضيلة (جامعة الوادي- University of Eloued, 2017)
This study seeks to highlight the behavior of Cement Institution of Tebessa from the Industrial Sector and its negative impact on the the environment through the Pollutants from the Cement Industry, which is one of the Polluting industries due to the emission of dust generated and to air pollution, both inside the plant or outside, so this institution made efforts in order to contribute to the development of preventive and Processing system for harm to the environment in the context of Investments to reduce Pollution as much as possible and tried to use cleaner Production techniques whenever possible, The study concluded that this Institution is committed to sustainable development within the framework of the development of an integrated Management System for Quality Management, Safety and the environment according to International Standards, The study recommended the continuation of this Institution to do devising new Processes and improve existing Methods in order to minimize the impact of this Industry on the environment, and try to disseminate and promote a culture of environmental Protection to all employees of the Institution.
The Behavior of the Cement Institution of Tebessa between the Dangers of the Environmental Pollutants for the Cement Industry and the Costs of facing them
مقال
Keywords: Environment, the Pollution, Environmental Pollution, Environmental Management, The Cement Industry